KMT-CPC Competition on Chinese National Identity Building: An Analysis of Contents and Discourses of and Editorials During Chinese Civil War - Jiru Zeng (SAGE Open)
Wars play a pivotal role in shaping national identity, especially when they engage all facets of a society. During the Chinese Civil War, both the Kuomintang (KMT), the ruling party, and the Communist Party of China (CPC), the major opposition party, leveraged the press to promote their competing visions of the Chinese nation. This study analyses editorials from the Central Daily News, the Xinhua Daily and the Liberation Daily to examine how the two parties emphasised different issues in national identity building, and framed varied discourses over politics, social development, ideology, culture, and enemies. The findings reveal three major dimensions of this competition: (1) the KMT’s conservative republicanism of ethnicities versus the CPC’s federalism of political parties, (2) divergent elucidations of Sun Yat-sen’s Three Principles of the People and (3) the opposing perceptions and identifications of China’s international status and enemies. Additionally, despite their shared ideological stance, the Xinhua Daily and the Liberation Daily exhibited notable differences in tone and word choice, which may indicate the complexity of the CPC’s mass communication strategy.